Financial Statement Analysis of PT Indofood Sukses Makmur Tbk Based on the Haval Analysis Framework - Fan Youwen (Journal of International Conference Proceedings, 2025)
This study evaluates the financial performance and strategic position of PT Indofood from 2020 to 2024 to examine its development trends and future prospects. Financial ratio analysis is applied to assess liquidity, solvency, profitability, efficiency, and growth, and the macro and micro environment. The results show that Indofood’s short-term solvency and capital structure improved steadily, profitability recovered after a downturn in 2022, and shareholder returns remained stable. However, operational efficiency declined, as reflected in slower receivables and inventory turnover, while revenue growth decelerated, indicating a maturing domestic market and intensifying competition. Overall, PT Indofood company demonstrates stable yet slowing growth. It is recommended that the company consolidate its domestic strengths while accelerating international expansion, particularly in Southeast Asia and Africa, and continuously innovate in healthy and functional food products to meet shifting consumer preferences. In addition, improving supply chain efficiency and employing financial instruments to hedge risks will be critical to sustaining resilience. By integrating financial and strategic analysis, this study provides a systematic evaluation of Indofood’s overall performance, offering practical insights for corporate decision-making as well as valuable reference for research on the food industry in emerging markets.